From hospital to cemetery: An analysis of unfinished mourning during the Covid-19 pandemic in Sanandaj - F. Mohammadi (Taḥqīqāt-i Farhangī-i Īrān)
The present research, using a qualitative approach, tries to examine the shaping components of unfinished mourning during the covid-19 pandemic in the city of Sanandaj. To achieve this goal, the concepts of worry, guilt, meaningful-meaningless death confrontation, the mental suffering of victims’ families and discourse were used as a conceptual framework. In the field study, the postmodern grounded theory was used whereas the data were gathered through in-depth qualitative interviews. Samples were selected through the purposive sampling method with the maximum variety and finally 15 participants were interviewed and the collected data were coded and analyzed in the form of eleven central categories. The results show that unfinished mourning are formed under the influence of spatial, technological, therapeutic-health, psychological, organizational-medical, social, cultural, discursive, philosophical-ideological and bureaucratic regulation components; in a way that the medical discourse, by shaping the laws of organizations and institutions such as cemeteries, hospitals and public places, causes the non-performance of burial rituals, funerals, obituaries, compliance with health protocols, drug consumption, avoidance of relatives and neighbors and family tensions.  In turn, it has led to the feeling of emptiness, meaninglessness of life, delaying relief and finally, the persistent grief of mourners. Therefore, the mourners’ experience during the pandemic is the experience of connection with the medical discourse and the social space, meaning that our social world can only be understood in the form of discourse.